Blood Cyst of the Mitral Valve Diagnosed in an Adult after Systemic Thrombolysis - Diana C. Ramírez-Mesías; Juan F. Contreras-Valero; Gabriel D. Pinilla-Monsalve; Carlos E. Vesga-Reyes (Case Reports in Cardiology)
Blood cysts in valves are very rare entities in adults, which can be distinguished through their echocardiographic features. A 57-year-old woman developed sudden dyspnea while hospitalized in the context of urinary sepsis; high-risk pulmonary embolism was diagnosed and she was prescribed systemic thrombolysis. She persisted with fever raising the suspicion of bacterial endocarditis. Transthoracic echocardiography did not report any masses, but later transesophageal imaging revealed a vegetation that was finally characterized as a blood cyst of the mitral valve based on ultrasound features. The patient evolved satisfactorily and did not require surgery.